2010
DOI: 10.1002/mnfr.201000048
|View full text |Cite
|
Sign up to set email alerts
|

Instant coffee with high chlorogenic acid levels protects humans against oxidative damage of macromolecules

Abstract: The oxidation of DNA, lipids and proteins associated with the incidence of various diseases and the protection against their oxidative damage may be indicative for beneficial health effects of coffee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
99
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 60 publications
8
99
1
8
Order By: Relevance
“…The present study found chlorogenic acid at 17.9 ± 1.3 g/g and caffeic acid at 23.2 ± 0.8 g/g in the stirfried chicken with green curry extract. Chlorogenic acid has been demonstrated to exhibit anti-inflammatory and antioxidant properties in vitro and in vivo [13][14]. Chlorogenic acid-rich coffee has been recently demonstrated to induce the Nrf2 (nuclear factor-erythroid 2-related factor-2)/antioxidant-response element (ARE) detoxifying pathway in vitro and in vivo [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found chlorogenic acid at 17.9 ± 1.3 g/g and caffeic acid at 23.2 ± 0.8 g/g in the stirfried chicken with green curry extract. Chlorogenic acid has been demonstrated to exhibit anti-inflammatory and antioxidant properties in vitro and in vivo [13][14]. Chlorogenic acid-rich coffee has been recently demonstrated to induce the Nrf2 (nuclear factor-erythroid 2-related factor-2)/antioxidant-response element (ARE) detoxifying pathway in vitro and in vivo [13].…”
Section: Discussionmentioning
confidence: 99%
“…Chlorogenic acid-rich coffee has been recently demonstrated to induce the Nrf2 (nuclear factor-erythroid 2-related factor-2)/antioxidant-response element (ARE) detoxifying pathway in vitro and in vivo [13]. In addition, humans consuming instant coffee at 800 ml/day for 5 days decreased oxidative stress markers 8-isoprostaglandin F2α by 15.3% and 3-nitrotyrosine by 16.1% in urine [14]. Caffeic acid phenethyl ester (CAPE) has been shown to exhibit anti-inflammatory activity in vitro and in vivo [15].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining four human intervention studies provided by the applicant (Bichler et al, 2007;Hoelzl et al, 2010;Misik et al, 2010;Steinkellner et al, 2005) used coffee types which had a composition different from that of C21. Two of these were single-arm intervention studies in eight (Bichler et al, 2007) and 10 (Steinkellner et al, 2005) subjects who consumed 600 mL or 1 L of coffee/day, respectively, for five days.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%
“…1) [3]. Несмотря на то, что изомеры ХГК значительно разрушаются в процессе обжа-ривания зерен [4,5], их содержание в раствори-мом кофе остается существенным и составляет 4-9 % [4,6,7].…”
Section: Introductionunclassified